2018
DOI: 10.4172/2252-5211.1000341
|View full text |Cite
|
Sign up to set email alerts
|

Legal Status of the Strategic Environmental Assessment (SEA), Practice of Application and Challenges in Pakistan

Abstract: The article entitled "Legal Status of the Strategic Environmental Assessment (SEA), Practice of Application and Challenges in Pakistan" has been accepted for publication in the International Journal of Waste Resources considering the statements provided in the article as personal opinion of the author which was found not having any conflict or biasness towards anything. As the article was a perspective one, information provided by the author was considered as an opinion to be expressed through publication. Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The highest proportion (42.3 per cent) of the respondents had moderate knowledge on SEA, while 32.7 per cent had good knowledge and only 25.0 per cent of the respondents had poor knowledge on SEA as a term. On the other hand, the highest proportion (59.6 per cent) of the respondents had poor knowledge on SEA conduction, while 24.0 per cent had moderate knowledge and only 16.3 per cent of the respondents had good knowledge on SEA conduction.The greatest proportion (56.7 percent) respondents possessed slightly favourable attitude while only 16.3 percent of the respondents had highly favourable attitude towards SEA.Ali et al [5] found also similar result from Pakistan and Omondi [8] from Kenya.…”
Section: Sea Profile Of the Respondentsmentioning
confidence: 70%
See 2 more Smart Citations
“…The highest proportion (42.3 per cent) of the respondents had moderate knowledge on SEA, while 32.7 per cent had good knowledge and only 25.0 per cent of the respondents had poor knowledge on SEA as a term. On the other hand, the highest proportion (59.6 per cent) of the respondents had poor knowledge on SEA conduction, while 24.0 per cent had moderate knowledge and only 16.3 per cent of the respondents had good knowledge on SEA conduction.The greatest proportion (56.7 percent) respondents possessed slightly favourable attitude while only 16.3 percent of the respondents had highly favourable attitude towards SEA.Ali et al [5] found also similar result from Pakistan and Omondi [8] from Kenya.…”
Section: Sea Profile Of the Respondentsmentioning
confidence: 70%
“…More or less similar condition also found in Pakistan, India, Sri Lanka etc. as south Asian countries [5,6].…”
Section: Practice Status Of Sea In Bangladeshmentioning
confidence: 99%
See 1 more Smart Citation
“…China and Pakistan need legal cooperation mechanisms and homogeneous commercial codes to make the infrastructure development of CPEC more reliable [83,84]. Through a literature survey of existing studies, the government of Pakistan needs to strictly adhere to a distinct growth plan by incorporating green information, communication and technology (ICT) for all projects under the head of CPEC [85,86].…”
Section: Recommendations and Conclusionmentioning
confidence: 99%